1998
DOI: 10.1021/ic980887o
|View full text |Cite
|
Sign up to set email alerts
|

Cation Catalysis of Anion−Anion Electron Transfer in Aqueous Solution:  Self-Exchange Reaction Kinetics of Some Hexa- and Octacyanometalate Couples at Variable Pressure

Abstract: Rate constants k ex for the Os(CN)6 3-/4-, Mo(CN)8 3-/4-, and W(CN)8 3-/4- self-exchange reactions in aqueous solution have been measured by 13C NMR as functions of pressure, temperature, and added electrolyte concentrations. Detailed interpretation of k ex values in the absence of added electrolytes is complicated by anion−cation association, but k ex is strongly influenced by the nature of added cations (Li+ < Na+ < K+ < Rb+ < Et4N+ < Cs+ ≤ Me4N+) and is linearly dependent on their concentrations. For K+ as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
66
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 71 publications
12
66
1
Order By: Relevance
“…z 1 z 2 = 30 (where z 1 and z 2 are 6 − and 5 − , the charges of ␣-2 1e and ␣-2 ox ), shows compliance with the extended Debye-Hückel equation, a prerequisite to the defensible application of theoretical models, such as those of Marcus and Sutin, to outer-sphere electron-transfer reactions between charged donors and acceptors. The parameters α and β used in the extended Debye-Hückel equation, are standard values for ions in water at 25 • C. The charge product of 29 ± 2 thus indicates that: (1) ␣-2 1e and ␣-2 ox behave in aqueous NaCl as charged, 6 − and 5 − , spheres, each with of radius 5.6Å [11], (2) ion pairing with Na + is negligible at NaCl concentrations as large as 1.1 M, and (3) that cation (Na + ) catalysis [21] of electron exchange between the two ions, is not kinetically significant.…”
Section: Electron Self-exchange Reactionsmentioning
confidence: 99%
“…z 1 z 2 = 30 (where z 1 and z 2 are 6 − and 5 − , the charges of ␣-2 1e and ␣-2 ox ), shows compliance with the extended Debye-Hückel equation, a prerequisite to the defensible application of theoretical models, such as those of Marcus and Sutin, to outer-sphere electron-transfer reactions between charged donors and acceptors. The parameters α and β used in the extended Debye-Hückel equation, are standard values for ions in water at 25 • C. The charge product of 29 ± 2 thus indicates that: (1) ␣-2 1e and ␣-2 ox behave in aqueous NaCl as charged, 6 − and 5 − , spheres, each with of radius 5.6Å [11], (2) ion pairing with Na + is negligible at NaCl concentrations as large as 1.1 M, and (3) that cation (Na + ) catalysis [21] of electron exchange between the two ions, is not kinetically significant.…”
Section: Electron Self-exchange Reactionsmentioning
confidence: 99%
“…These findings support a reaction mechanism previously proposed for other anion-anion electron transfer reactions, catalyzed by alkali metal ions, that catalysis is facilitated by partially dehydrated M þ . 141 …”
Section: Other Reactionsmentioning
confidence: 99%
“…The mechanism of water-dependent electroactivity is rooted in the different e À transfer pathways exhibited by cyanometallates [21,57]. The cation-dependent e À transfer pathway is orders of magnitude faster than the cationindependent pathway [23]. We postulate that the Fe(CN) 6 4À/ 3À can exist as ion pairs with NH 3 R þ when water is not present.…”
Section: Voltammetry In Organic Solventsmentioning
confidence: 99%
“…The uncatalyzed selfexchange reaction is 4 orders of magnitude slower [22]. Swaddle has suggested that volumes of activation are consistent with partial deaquation of the cation during the electron-transfer reaction [20,23,24]. Swaddle showed a linear dependence of the magnitude of the self-exchange reaction on the concentration of uncomplexed, aquated K at an electrode or between microelectrodes would be necessary.…”
Section: Introductionmentioning
confidence: 98%